2021
DOI: 10.18632/aging.203047
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA RUSC1-AS1 promotes osteosarcoma progression through regulating the miR-340-5p and PI3K/AKT pathway

Abstract: Dysregulation of long noncoding RNA (lncRNA) is frequently involved in the progression and development of osteosarcoma. LncRNA RUSC1-AS1 is reported to be upregulated and acts as an oncogene in hepatocellular carcinoma, cervical cancer and breast cancer. However, its role in osteosarcoma has not been studied yet. In the present study, we investigated the role of RUSC1-AS1 in osteosarcoma both in vitro and in vivo . The results showed that the expression of RUSC1-AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For instance, UNC5B-AS1 promotes the malignant progression of hepatocellular carcinoma, ovarian cancer, prostate cancer, lung cancer, and thyroid cancer ( 36 40 ). Notably, the tumor promotion role of RUSC1-AS1 has been well-characterized in OS ( 41 , 42 ). Rui Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, UNC5B-AS1 promotes the malignant progression of hepatocellular carcinoma, ovarian cancer, prostate cancer, lung cancer, and thyroid cancer ( 36 40 ). Notably, the tumor promotion role of RUSC1-AS1 has been well-characterized in OS ( 41 , 42 ). Rui Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found to be upregulated in osteosarcoma in the same study as COX10-AS1, which is mentioned above [ 95 ]. There are many more studies exploring its interactions with miRNAs in tumor progression [ 97 , 98 ]. In the present systematic review, it was found to be upregulated in patients with Sertoli cell-only syndrome [ 29 ], and deregulated in asthenozoospermia [ 41 ] and oligozoospermia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rno-mir-340-5p and rno-mir-21-5p presented many target genes enriched in the PI3K-Akt signaling pathway, which is closely related to corneal transplantation rejection. Additionally, rno-mir-340-5p plays a role in the progression of osteosarcoma through the PI3K Akt pathway [20]. However, the mechanisms of rno-mir-340-5p/PI3K-Akt have been rarely reported.…”
Section: Discussionmentioning
confidence: 99%